THE IMPACT OF ARTIFICIAL INTELLIGENCE FOR COMING YEARS AND THE NEW TYPES OF JOB WHICH DEPEND ON IT. (THE DOMAIN OF MEDICINE AND JOURNALISM , DIGITAL TECHNOLOGY ARE INCLUDED IN THIS ARTICLE) - Askarova Mokhichekhra (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
-